Characteristics of Ketapang Urban Aquaculture as a Tourism Destination in Tangerang Regency, Banten Province - Yanuadi, Ardiatno; Lilis Sri Mulyawati; Indarti Komala Dewi (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2024)
Abstract. This research is driven by the great potential of tourism in improving the economy and affecting social and environmental aspects in Ketapang Urban Aquaculture (KUA). Although, the number of tourists tends to decrease. Therefore, this study aims to analyze the existing conditions in the main aspects of the 4A (Attractions, Amenities, Accessibility, and Ancillary) and analyze the perception of tourists so that it can be known what aspects need to be improved. The existing condition of KUA was analyzed using the descriptive analysis method, while the perception of tourists was analyzed using the scoring method. Analysis of existing conditions shows that KUA has a unique attraction: a mangrove park integrated with shrimp cultivation areas. KUA has an iconic amenity: the main building is shaped like a horseshoe crab and a Mangrove Plaza. The condition of the road to KUA is quite good and equipped with signposts. Analysis of tourist perception on the aspect of attraction with the highest score (1.97), namely mangrove park attractions, the lowest score (1.24) for mangrove plant education activities. The amenity aspect with the highest score (2.23) is cleanliness, and the lowest score (1.20) is for toilet facilities. The accessibility aspect of the highest score (2.54) is the main gate, and the lowest score (1.36) is the availability of public transportation modes. The ancillary aspect has the highest score (1.77) in management, and the lowest score (1.29) is promotion.